Adsorption of dyes onto palygorskite and its composites: a review - Mu, B.; Wang, A.
With the continuous increase in the demand of dyes, the dye wastewater is becoming a major environmental threat. Adsorption techniques are widely used to remove dyes from wastewater using clay minerals, especially a naturally available one-dimensional palygorskite due to high surface area, moderate cation exchange capacity, excellent salt resistance compared with other clay minerals. Although the maximum adsorption of natural palygorskite toward dyes far exceeded the cation exchange capacity of palygorskite, it is difficult to completely release the adsorption capacity of palygorskite toward dyes due to the existence of the bulk crystal bundles or aggregates originated from the interparticle Van der Waals' and hydrogen bonding interactions. Therefore, it is indispensible to disaggregate palygorskite crystal bundles and introduce functional groups to improve the microscopic structure of palygorskite and increase the adsorption sites via various physical and chemical modifications. This review article summarizes the development on the modified palygorskite with different physical or chemical methods and palygorskite-based composite used as adsorbents for the adsorption of dyes from aqueous solution by reviewing a comprehensive literature combined with our group's research achievements. In addition, few conclusions and suggestions have been proposed for future research.
Keywords: PALYGORSKITE; ACTIVAITION; MODIFICATION; COMPOSITE; DYE ADSORPTION